IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE NHT LEARNING MODEL IN FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Nuraini Nuraini (Universitas Tadulako, 2019)
The problem in this study is the low value of student learning outcomes in science subjects in the fifth grade of SD Inpres 1 Tomoli. One of the factors that causes is the method of teaching that is less attractive, so the results of teaching and learning activities become less effective. researchers used the NHT type cooperative learning model to improve class student learning outcomes. This research was conducted in two cycles and each cycle consisted of two meetings. The results of the study in the first cycle with the percentage of classical completeness of 62.96% with an average value of 69.96%. The results of observation of teacher activities in the first cycle amounted to 78.26% or in the good category and the results of observations of student activities in the first cycle amounted to 81.52% or in the very good category. The results of the first cycle have not reached the Minimum Completion Criteria in this study which is 70 and the Classical Learning Criteria is 70%, so that it is continued in cycle II. In the second cycle the percentage of classical completeness was 85.18% with a score of 79.62 and the results of observation of teacher activities were 84.78% or in the very good category and the results of observations of student activities were 89.18% or in the very category well. Based on the improvement in learning outcomes, it can be concluded that by using the NHT type cooperative learning model can improve student learning outcomes in class V SD Inpres 1 Tomoli.